Mesoteloblast-like mesodermal stem cells in the polychaete annelid Platynereis dumerilii (Nereididae) - Fischer, Antje; Arendt, Detlev (Journal of experimental zoology. Part B, Molecular and developmental evolution, 2013)
Spiral cleavage is observed in animals that belong to the lophotrochozoa, a large group of marine invertebrates. As characteristic for spiral cleavage, the bulk of mesoderm forms from one cell, the “4d blastomere.” This process has not yet been followed in cellular detail in annelids except in the leech, where “mesoteloblasts,” a pair of mesodermal stem cells, generate two bands of mesoderm precursor cells in an iterative fashion. It is so far unknown whether such stem cell-like lineage is a general property of 4d-derived mesoderm in spiralian larvae. To address this, we have analyzed the cell lineage of the 4d blastomere in the polychaete annelid Platynereis dumerilii, an emerging model for lophotrochozoan and spiralian embryology (Fischer et al., 2010), by 4D microscopy, a semi-automated cell tracking technique based on differential interference contrast serial imaging (Schnabel et al. '97). Our data reveal that the two daughter cells of the 4d cell undergo seven consecutive rounds of unequal cell divisions. They bud off smaller cells in ventral-vegetal orientation and thus show mesoteloblast- and stem cell-like behavior. Based on these findings, we suggest that mesoteloblast-like mesodermal stem cells that form continuous mesodermal bands are part of the Errantia + Sedentaria ground pattern. In the course of annelid evolution, the number consecutive divisions of these cells would have been low initially with <10 division cycles, giving rise to larval segments only, and then increased up to 35 as observed in clitellates. J. Exp. Zool. (Mol. Dev. Evol.) 320B:94-104, 2013. © 2013 Wiley Periodicals, Inc.